Nano Transition Metal Sulfide Catalyst for Solvolysis Liquefaction Soda Lignin - Fei-Ling Pua,; Chin-Hua Chia,; Sarani Zakaria,; Soon-Keong Neoh,; Tze-Khong Liew, (Faculty of Science and Technology, UKM, 2011)
Solvolysis liquefaction of soda lignin in the presence of various transition metal sulfide catalysts was studied to investigate the catalyst effects on the oil and gas yields, conversion rate and higher heating value (HHV) of oil. Nanosized copper sulfide, iron sulfide and molybdenum sulfide were successfully synthesized via a simple hydrothermal method under reaction temperature 200°C for 90 min. The addition of transition metal sulfide based catalysts (CuS, MoS2 and FeS2) enhanced both production of the oils and gas and the higher heating value (HHV) of oil products. A high oil and gas yields of 82.1% and 2890 cm3 was obtained with MoS2 at 250°C for 60 min. Elemental analyses for the oils revealed that the liquid products have much higher heating values than the crude soda lignin powder.